Sensor data cleaning for applications in dairy herd management and breeding - Schodl, Katharina; Stygar, Anna; Steininger, Franz; Egger-Danner, Christa (Frontiers in Animal Science, 2024)
Data cleaning is a core process when it comes to using data from dairy sensor technologies. This article presents guidelines for sensor data cleaning with a specific focus on dairy herd management and breeding applications. Prior to any data cleaning steps, context and purpose of the data use must be considered. Recommendations for data cleaning are provided in five distinct steps: 1) validate the data merging process, 2) get to know the data, 3) check completeness of the data, 4) evaluate the plausibility of sensor measures and detect outliers, and 5) check for technology related noise. Whenever necessary, the recommendations are supported by examples of different sensor types (bolus, accelerometer) collected in an international project (D4Dairy) or supported by relevant literature. To ensure quality and reproducibility, data users are required to document their approach throughout the process. The target group for these guidelines are professionals involved in the process of collecting, managing, and analyzing sensor data from dairy herds. Providing guidelines for data cleaning could help to ensure that the data used for analysis is accurate, consistent, and reliable, ultimately leading to more informed management decisions and better breeding outcomes for dairy herds.